2019
DOI: 10.1590/0001-3765201920171023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microhabitat on the richness of anuran species: a case study of different landscapes in the Atlantic Forest of southern Brazil

Abstract: Influence of microhabitat on the richness of anuran species: a case study of different landscapes in the Atlantic Forest of southern Brazil. An Acad Bras Cienc 91: e20171023.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Breeding site configuration, such as pond descriptors, for example, would play a bigger role than land use over tadpole species diversity (Dalmolin et al 2020). Although we have no detailed data to support this hypothesis, several studies have shown that microhabitat characteristics affect amphibian richness (D’Anunciação et al 2013; Knauth et al 2018; Figueiredo et al 2019). Forest heterogeneity, leaf litter depth, canopy cover and presence of clearings are examples of local descriptors that are not detected at a landscape level but affect anuran species composition (Ferrante et al 2017; Howell et al 2019).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Breeding site configuration, such as pond descriptors, for example, would play a bigger role than land use over tadpole species diversity (Dalmolin et al 2020). Although we have no detailed data to support this hypothesis, several studies have shown that microhabitat characteristics affect amphibian richness (D’Anunciação et al 2013; Knauth et al 2018; Figueiredo et al 2019). Forest heterogeneity, leaf litter depth, canopy cover and presence of clearings are examples of local descriptors that are not detected at a landscape level but affect anuran species composition (Ferrante et al 2017; Howell et al 2019).…”
Section: Discussionmentioning
confidence: 80%
“…At the same time, these habitat changes favor the colonization by species such as Boana faber and Dendropsophus minutus (Aquino et al 2004, 2010; Scott et al 2004; Lavilla et al 2010; Silvano et al 2010). These species are often found in fragmented landscapes and expanding open areas (Preuss 2018; Figueiredo et al 2019; Menin et al 2019). We also recorded the exotic bullfrog ( Lithobates catesbeianus ) in four of the seven remnants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades many studies were developed on anuran amphibian communities from different physiognomies of the Atlantic Rainforest biome (e.g, Heyer et al 1990, Canelas & Bertoluci 2007, Araújo et al 2010, Brassaloti et al 2010, Forlani et al 2010, Vilela et al 2011, Figueiredo et al 2019. Population declines and even local extinctions were detected in some localities, such as Santa Tereza, in Espírito Santo state (Weygoldt 1989), and Serra do Japi (Haddad & Sazima 1992), Estação Biológica de Boracéia (Heyer et al 1988, 1990, Bertoluci & Heyer 1995, Verdade et al 2011 and Estação Biológica do Alto da Serra de Paranapiacaba (Verdade et al 2009), in São Paulo state, which show the importance of ecological studies, even in wellstudied regions, such as southeastern Brazil (Haddad & Prado 2005, Brito 2008, Verdade et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, habitat characteristics influence the spatial and temporal distributions of species (Campos, Trindade-Filho, Brito, Llorente, & Solé, 2014;Ferreira, Beard, & Crump, 2016;Figueiredo, Storti, Lourenço-de-Moraes, Shibatta, & Anjos, 2019;Hawkins, 2001). Thus, historical dispersal can be understood using environmental data of the localities at which species have been recorded and the geographical boundaries that restrict them (Gaston, 1991).…”
Section: Introductionmentioning
confidence: 99%